2018
DOI: 10.4236/ojap.2018.74014
|View full text |Cite
|
Sign up to set email alerts
|

Emission of Carbonaceous Species from Biomass Burning in the Traditional Rural Cooking Stove in Bangladesh

Abstract: Characterization of carbonaceous species from the particulate matters (PM) after combustion of seven commonly used biomass species, albizia tree (Albizia julibrissin), dry leaves (mahogany tree), jackfruit tree (Artocarpus heterophyllus), rain tree (Samanea saman), mahogany tree (Swietenia mahogany), cow dung and mango tree (Mangifer aindica) was done. PM samples were collected on quartz fiber filters emitted from biomass burning in a typical rural cooking stove. PM loaded filters were characterized with scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…The average BC concentration during the campaign was 13 ± 6 μg m –3 , which is among the highest in the world . Even so, it is somewhat lower compared to previous measurements in the same area , but higher than what is observed at an IGP receptor site (4.6 ± 3.9 μg m –3 ) north of the Bay of Bengal . A reason for the lower values reported in this study compared to earlier studies for Dhaka may be that the present measurements were conducted in fine-mode aerosols, while previous measurements were in total suspended particulate matter.…”
Section: Resultscontrasting
confidence: 83%
“…The average BC concentration during the campaign was 13 ± 6 μg m –3 , which is among the highest in the world . Even so, it is somewhat lower compared to previous measurements in the same area , but higher than what is observed at an IGP receptor site (4.6 ± 3.9 μg m –3 ) north of the Bay of Bengal . A reason for the lower values reported in this study compared to earlier studies for Dhaka may be that the present measurements were conducted in fine-mode aerosols, while previous measurements were in total suspended particulate matter.…”
Section: Resultscontrasting
confidence: 83%
“…The BrC effect may have some direct radiative climate‐related significance in geographically limited regions where the biomass burning is steady, like in regions where wooden stoves are used daily for cooking or heating purposes (Ahmed et al, ; Feng et al, ). The cooling/warming regime may also change by considering the semidirect and indirect aerosol effects (e.g., Jacobson, ), which are not considered in this study.…”
Section: Direct Radiative Forcing By Biomass Burning Aerosolsmentioning
confidence: 99%
“…Before the burning, all the biomasses were cut into small pieces and dried on the roof of the Mukarram Hussain Khundaker Science Building, Dhaka University. All the sampling was done in the Environmental and Atmospheric Chemistry Laboratory, at Dhaka University, Bangladesh, according to the previous report (Ahmed et al 2018, Pavel et al 2023. The experimental procedure is given below (figure 1).…”
Section: Sample Collection and Sampling Proceduresmentioning
confidence: 99%
“…However, our study identified the optical characteristics of the dust that mosquito coils release. Around 70% of the people of Bangladesh live in the village and they use biomasses as fuel for their cooking purposes and unwillingly produce large amounts of BrC and BC particles in the ambient atmosphere (Ahmed et al 2018). These particles absorb light and increase the temperature of the atmosphere.…”
Section: Introductionmentioning
confidence: 99%